Randomized controlled study to evaluate the safety and clinical impact of percutaneous auricular vagus nerve stimulation in patients with severe COVID-19 - Seitz, Tamara; Bergmayr, Franziska; Kitzberger, Reinhard; Holbik, Johannes; Grieb, Alexander; Hind, Julian; Lucny, Felix; Tyercha, Alexander; Neuhold, Stephanie; Krenn, Claus; Wenisch, Christoph; Zoufaly, Alexander; et al. (Frontiers in Physiology, 2023)
Introduction: A severe course of COVID-19 is characterized by a hyperinflammatory state resulting in acute respiratory distress syndrome (ARDS) or even multi-organ failure along a derailed sympatho-vagal balance.Methods: In this prospective, randomised study, we evaluate the hypothesis that percutaneous minimally invasive auricular vagus nerve stimulation (aVNS) is a safe procedure and might reduce the rate of clinical complications in patients with severe course of COVID-19. In our study, patients with SARS-CoV-2 infection admitted to the intensive care unit (ICU) with moderate to severe ARDS, however without invasive ventilation yet, were included and following randomisation assigned to a group receiving aVNS 4 times per 24hours for 3 hours and a group receiving standard of care (SOC).Results: 12 patients were included in total (6 in aVNS and 6 in SOC group). No side effects aVNS were reported, especially no significant pain at device placement or during stimulation at stimulation site or significant headache or bleeding after or during device placement or lasting skin irritation. There was no significant difference in the aVNS and SOC group between length of stay in the ICU and at the hospital, bradycardia, delirium or 90-day mortality. In the SOC group 5 of 6 patients required invasive mechanical ventilation during their stay at hospital and 60% of them venovenous extracorporeal membrane oxygenation (vvECMO), compared to 3 of 6 patients and 0% in the aVNS group (p=0.545 and p=0.061).Discussion: Vagus nerve stimulation in patients with severe COVID-19 is a safe and feasible method. Our data showed a trend to a reduction of progression to need of invasive ventilation and vvECMO which encourages further research with larger patient samples.